Anabolics steroids in a physical education undergraduate program: an ethical-sanitary dilemma among bodybuilder students - Eduardo Pinto Machado; Alex Branco Fraga (Journal of Physical Education (Maringá), 2020)
This article deals with the dilemma faced by physical education student-bodybuilders who are dedicated to learning on their own about the uses of anabolic steroids for non-therapeutic purposes. The concept of the ethical-sanitary dilemma is developed from the articulation between Nikolas Rose's concept of expertise and Deborah Lupton's concept of risk. Episodic interviews with six undergraduate students of Physical Education from a Brazilian university were applied in this study as the principal method. As a result, we identified two profiles of student-bodybuilders: one composed of those who joined the program in order to learn how to use anabolic steroids, and another one composed of those who presumed to know about the uses and whose purpose was to earn an undergraduate diploma. We conclude that the ethical-sanitary dilemma observed in both profiles should be addressed in the Physical Education undergraduate courses since the “curricular silence” on the process of muscular hypertrophy via steroid anabolics, associated with the clandestine atmosphere, may add more misinformation and even more risks to the target audience of this study.